JURIDICAL ANALYSIS OF THE APPLICATION OF THE ELEMENTS OF CONTINUING ACTION (STUDY OF THE CASE ON BEHALF OF THE DEFENDANT RUDIYANTO BIN CARTA WHO WAS CHARGED WITH VIOLATING ARTICLE 374 IN CONJUNCTION WITH ARTICLE 64 OF THE CRIMINAL CODE AT THE NORTH JAKART (JURNAL HUKUM DAS SOLLEN, 2023)
The type of research in this study is normative research with an approach in the form of statutory regulations (statue approach) and a conceptual approach (conceptual approach). Data collection techniques in normative legal research are carried out by means of literature study on legal materials, both primary legal materials, secondary legal materials and tertiary legal materials through library research. The results of the study revealed that the acts continued/concurrently committed criminal acts (types of combined offenses), as referred to in Article 63 paragraph (1) of the Criminal Code concerning Combinations in an Act (Concursus Idealis), Article 64 of the Criminal Code concerning Continuing Actions and Articles 65 to Article 69 of the Criminal Code concerning Combination in Several Actions (Concursus Realis). The application of the continuance act article in the indictment is incorrect, because it does not fulfill the element of the continual act, especially the element "which is related in such a way". The Public Prosecutor did not include elements of continuing actions in the verdict of the case, because it was clearly not in accordance with the legal facts contained in the case files and evidence, and if examined more deeply the actions committed by the Defendant fulfilled more of the Concursus Realis element (Article 65 of the Criminal Code) because every act committed by the Defendant has been completed and any money embezzled by the Defendant is directly spent or used by the Defendant not to be "saved" or "saved" for some purpose in the future. The actions of the Defendant were inappropriate if in conjunction with Article 64 paragraph (1) of the Criminal Code by the Public Prosecutor because the elements of the act continued.